2018
DOI: 10.1371/journal.pone.0207085
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of lipopolysaccharide-induced preterm labor by the lack of CX3CL1-CX3CR1 interaction in mice

Abstract: Preterm labor (PTL) is the most common cause of neonatal death and long-term adverse outcome. The pharmacological agents for PTL prevention are palliative and frequently fail to prevent PTL and improve neonatal outcome. It is essential to fully understand the molecular mechanisms of PTL in order to develop novel therapeutic methods against PTL. Several lines of evidence indicate some chemokines are expressed in gestational tissues during labor or PTL. To reveal the pathophysiological roles of the CX3CL1-CX3CR1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…LPS-mediated inflammatory response is clearly correlated to prematurity or fetal loss [3942]. A role of the CX3CL1-CX3CR1 chemokine signaling pathway through intrauterine recruitment of macrophages and the enhancement of macrophage-derived inflammatory mediators was recently demonstrated in LPS-induced PTL in mice [43].…”
Section: Introductionmentioning
confidence: 99%
“…LPS-mediated inflammatory response is clearly correlated to prematurity or fetal loss [3942]. A role of the CX3CL1-CX3CR1 chemokine signaling pathway through intrauterine recruitment of macrophages and the enhancement of macrophage-derived inflammatory mediators was recently demonstrated in LPS-induced PTL in mice [43].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, IL-27R signaling contributed to Ly6G + neutrophils accumulation in diseased aorta of mice model with aortic aneurysm [24]. Our previous work had suggested that IL-27 can promote the in ammatory process of human FMs in preterm labor [17]. Therefore,we speculated that IL-27 could contribute to the increased in ammation by affecting neutrophils in ltration at the maternal and fetal interface.…”
Section: Discussionmentioning
confidence: 93%
“…The vaginal plugs were checked the next morning, whose presence indicated gestational day of 0.5. The mice model of PTLI was established as previously reported [16,17]. Brie y, at gestational day of 16.5, the pregnant mice were intraperitoneally administered with LPS (25μg in 200μl PBS) or PBS 200μl.…”
Section: Human Samplesmentioning
confidence: 99%
“…Furthermore, compared to women not in labour, women at term in labour or women in PTL display a high density of tissue resident macrophages [ 36 ]. Most significantly, it has been shown that macrophage depletion in a rodent model prevents infection-induced PTL [ 37 , 38 ] and cervical remodelling [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%